MiFID II and MiFIR: stricter rules for the EU financial markets. Issue 2 (3rd July 2017) - Busch, Danny
Abstract : This article analyses and discusses the new MiFID II and MiFIR rules for the EU financial markets. In particular, it analyses the concepts "regulated market", "Multilateral Trading Facility" (MTF), "Organised Trading Facility" (OTF) and "(systemic) internalisation". It also discusses (i) pre-trade and post-trade transparency, (ii) transaction reporting, (iii) data services providers, (iv) concentration of trading, (v) position limits, and (vi) position management powers in the case of trading in commodity derivatives and reporting obligations.